PENERAPAN MEDIA JAM UNTUK MENINGKATKAN NUMERASI SISWA SEKOLAH DASAR MABHAMBAWA (STUDI KOLABORATIF GERAKAN NUMERASI SEKOLAH) - Meo, Thomas Didimus; Qondias, Dimas; Wau, Maria Patrisia; Noge, Maria Desidaria (Dharmas Education Journal (DE_Journal), 2024)
This study is based on the low numeracy levels of elementary school students observed and interviewed during the implementation of the sixth cohort of the Teaching Campus program. This situation is suspected to be due to suboptimal numeracy activities and the need for more utilization of authentic learning resources. The study aims to improve numeracy using clock media for elementary school students. This research employs a qualitative method, with data collection techniques including observation, interviews, and documentation. The results of implementing clock media show that 89% of students have understood the concept of time, while 11% still need to. The increase before and after the implementation of clock media is 66%. This significant improvement emphasizes the importance of using visual and interactive media to enhance the numeracy of elementary school students.